Prevalence of bullying among pupils in Baghdad - Waleed Arif Tawfeeq Al-Ani,; Ahmed Khalaf Al-Delaimy,; Yossra Hanoon Al-Robaiaay,; Reem Falah Kadhim, (Journal of the Pakistan Medical Association, 2024)
Objective: To find out the prevalence of bullying among primary school students in an urban centre, and to categorise its types. Method: The descriptive, cross-sectional study was conducted from October 1, 2018, to March 31, 2019, in Baghdad, Iraq, and comprised primary school children of either gender aged 9-15 years studying in schools in all the 3 directorates of the Al-Karkh side of the city. Data was collected through face-to-face interviews with the subjects, from school data, and through interaction with social-guide teachers of the respective classes. Data was analysed using SPSS 28. Results: Of the 1,000 subjects from 50 schools, 537(53.7) were girls, 322(32.2%) were aged 11 years and 409(40.9%) were in the fifth grade. Overall, 146(14.6%) students reported having been bullied, 29(2.9%) were bullies themselves, while 59(5.9%) were both bullies and the bullied. It was found that almost quarter of pupils take part in bullying other pupils and almost 20% of pupils were kicked, pushed or hit by other Pupils during the last month. Conclusion: Bullying was found to be prevalent in the study's sample. No clear legislation is present to prevent or control the social problem that has a significant effect on the mental and behavioural burden on students. Key Words: Bullying, Students, Schools, Social Problems.